Genealogi Pemikiran Pendidikan KH. Hasyim Asy'ari - Khasanah, Uswatun; Waskito, Tejo (Universitas Islam Negeri Raden Intan Lampung, 2019)
The current problem of education is the low morality and bluntness of rationality. This morality problem as well as rationality should be the encouragement of researchers to examine the thoughts of Hasyim Asy'ari as a thinker who has great concern for the education and morality of the Ummah. This figure titled Hadratussyaikh poured his thoughts through a classic book taught at the salaf pesantren. One of his phenomenal works is the book Adab al- ‘Alim wa Muta’allim. This article aims to explore the lineage of thought of Hasyim Asy'ari in the context of educational thinking. The method used is a study of historical analysis. This study produced three findings; first, the genealogy of educational thought of Hasyim Asy'ari was formed by a touch of the thoughts of ulama directly forming the religious views of Hasyim Asy'ari such as the thoughts of Khalil Bangkalan, Nawawi al-Bantani, Mahfudz at-Tirmisi and Khatib Minangkabawi; second, Hasyim Asy'ari's educational thought relations were influenced by the thinking of medieval classical scholars (traditionalism) precisely by the thoughts of al-Ghazali and al-Zarnuji; thus it can be concluded that in studying science it is important to be selective in choosing teachers. because a good scientist cannot be separated from the guidance of good teachers.